Information Security Architecture: An Integrated Approach to Security in the Organization, Second Edition - Killmeyer Tudor, Jan (CRC Press, 2009)
Information Security Architecture, Second Edition incorporates the knowledge developed during the past decade that has pushed the information security life cycle from infancy to a more mature, understandable, and manageable state. It simplifies security by providing clear and organized methods and by guiding you to the most effective resources available.